A educação e os multiletramentos: leitura e escrita de linguagem multissemiótica no hipertexto blog - Alves , Teresa Cristina (2015)
Life of Human beings, currently, is totally linked to new technologies which, definitely, come to stay, attracted people attention. Those technologies made daily activities easier and faster. All these facilities propose a virtual environment a place of interaction and research, particularly concerning how language is handle by youth. In this context, the way to develop teaching school has been hard and considered like a disadvantage competition being school far from away student’s reality: these use technologies frequently day by day. Considering this fact, we decided to work on this issue in a primary school in the city of João Pessoa, with the main objective, to understand that the use of the media favors the educational practice, when the orientation is focused to the conscious use of the virtual environment to encourage research and systematization of information on the network for the construction of knowledge. Seeing all these statements, we took as theorical background of studies as Levi (2010), Schmitd-Cohen (2013), Moran (2010), among others, these scholar brings important contributions about how technologies as a big phenomena and the urgent modification education environment has to receive, in order can follow this evolutionary process. We also saw studies that underground literacies practices at school, hypertext and multiliteracies concepts. To do that we looked at Marcuschi (2010), Antunes (2003), Xavier (2010)and Rojo (2012), among others scholars. Based on these studies and based on approaches, we realized a research using questionnaires to teachers and students to bound the plot around school/field in Action Research. From this view, we elaborate and developed a pedagogical intervention as searching with didactical sequences just in what is proposed by Schenewly and Dolz (2004) In the early period of sequence, students ninth grade from mentioned school used their previous knowledge about technology to produced videos on semiotics language. They also produced a first version of electronic genre/support Blog. After analyze and reflection about these first productions in modularization period, they received pedagogical support on multiliteracies form to change they knew previously, leaning new concepts and new language production, reflecting about written and making communication on specific functions and goals. At the final production there was a presentation to school community of the Blog “Portal S. A, conscientizando vidas”, electronic genre which lead like a support to publicize their productions. The experience was measured by school like in order to not only for develop communicative competences in our students but also it provides innovator technology contemporary uses as a great helper for teaching and learning construction.